Clinical outcomes of stereotactic body radiotherapy for stage I non-small cell lung cancer using different doses depending on tumor size - Baba, Fumiya (BioMed Central, 2010)
BACKGROUND: The treatment schedules for stereotactic body radiotherapy (SBRT) for lung cancer vary from institution to institution. Several reports have indicated that stage IB patients had worse outcomes than stage IA patients when the same dose was used. We evaluated the clinical outcomes of SBRT for stage I non-small cell lung cancer (NSCLC) treated with different doses depending on tumor diameter. METHODS: Between February 2004 and November 2008, 124 patients with stage I NSCLC underwent SBRT. Total doses of 44, 48, and 52 Gy were administered for tumors with a longest diameter of less than 1.5 cm, 1.5-3 cm, and larger than 3 cm, respectively. All doses were given in 4 fractions. RESULTS: For all 124 patients, overall survival was 71%, cause-specific survival was 87%, progression-free survival was 60%, and local control was 80%, at 3 years. The 3-year overall survival was 79% for 85 stage IA patients treated with 48 Gy and 56% for 37 stage IB patients treated with 52 Gy (p = 0.05). At 3 years, cause-specific survival was 91% for the former group and 79% for the latter (p = 0.18), and progression-free survival was 62% versus 54% (p = 0.30). The 3-year local control rate was 81% versus 74% (p = 0.35). The cumulative incidence of grade 2 or 3 radiation pneumonitis was 11% in stage IA patients and 30% in stage IB patients (p = 0.02). CONCLUSIONS: There was no difference in local control between stage IA and IB tumors despite the difference in tumor size. The benefit of increasing the SBRT dose for larger tumors should be investigated further.